Alien ectomycorrhizal plants differ in their ability to interact with co-introduced and native ectomycorrhizal fungi in novel sites - Vlk, Lukáš; Tedersoo, Leho; Antl, Tomáš; Větrovský, Tomáš; Abarenkov, Kessy; Pergl, Jan; Albrechtová, Jana; Vosátka, Miroslav; Baldrian, Petr; Pyšek, Petr; Kohout, Petr (The ISME journal, 2020)
Alien plants represent a potential threat to environment and society. Understanding the process of alien plants naturalization is therefore of primary importance. In alien plants, successful establishment can be constrained by the absence of suitable fungal partners. Here, we used 42 independent datasets of ectomycorrhizal fungal (EcMF) communities associated with alien Pinaceae and Eucalyptus spp., as the most commonly introduced tree species worldwide, to explore the strategies these plant groups utilize to establish symbioses with EcMF in the areas of introduction. We have also determined the differences in composition of EcMF communities associated with alien ectomycorrhizal plants in different regions. While alien Pinaceae introduced to new regions rely upon association with co-introduced EcMF, alien Eucalyptus often form novel interactions with EcMF species native to the region where the plant was introduced. The region of origin primarily determines species composition of EcMF communities associated with alien Pinaceae in new areas, which may largely affect invasion potential of the alien plants. Our study shows that alien ectomycorrhizal plants largely differ in their ability to interact with co-introduced and native ectomycorrhizal fungi in sites of introduction, which may potentially affect their invasive potential.
Keywords: rostliny; mykorhiza; stromy; Plants; Mycorrhizae; symbióza; Trees; Introduced Species; Symbiosis; zavlečené druhy